Induced mutations in crop plants : mutants of scientific and/or agronomic interest at the Institute of Genetics “Ewald A. Favret” = Mutaciones inducidas en plantas cultivadas : mutantes de interés interés científico y/o agronómico en el Instituto de Genética “Ewald A. Favret” - Landau, Alejandra Mabel (2021)
The use of induced mutations techniques in crop plants at Instituto de Genética "Ewald A. Favret" (IGEAF) INTA, started in 1949, with the pioneer work of Ewald Favret, who studied the effects of physical and chemical mutagens on barley (Hordeum vulgare) and wheat (Triticum aestivum). IGEAF contributed with several novel results about the effects of important chemical mutagens such as ethyl methane sulfonate (EMS) and sodium azide, and their interactions with X-rays, on barley and wheat. During several decades, a good deal of the research was directed to study the relationship between the different effects of mutagenic treatments on the M1 and subsequent generations, and its implications for efficient selection of induced mutants. Many original barley and wheat mutants have been isolated at IGEAF, which early on contributed to elucidate the genetic basis of characters like the hormonal control of growth, the grain protein content and diseases reactions. Besides, several other novel mutants were isolated and characterized including genetically unstable mutants, which are able to originate new heritable variability. One of these mutants is the barley chloroplast mutator (cpm) from which some interesting mutants have been isolated. Moreover, a high throughput strategy for the screening of plastome mutants originated by the cpm was developed (cpTILLING) that allowed the detection of 61 different mutational events, showing the cpm as an extraordinary source of plastome mutants. On the other hand, protocols for direct selection of wheat mutants tolerant to drought were developed and promising advanced lines are at present investigated. Furthermore, a mutant allele of the AHAS (acetolactate synthase) gene in wheat conferring imidazolinones herbicides tolerance, was isolated. The incorporation of this allele to other genetic backgrounds showed increased levels of tolerance, which in one family were observed in association with increased Fusarium tolerance. In addition to the work done in barley and wheat, interactions with several breeding programs in other crops were carried out. Finally, some commercial achievements of INTA obtained by using induced mutations techniques are briefly described; being the most important the case of the INTA rice (Oryza sativa) breeding program for developing imidazolinones tolerant commercial varieties that in recent years covered 70% of the irrigated rice area in Latin America.